The 240Pu(n,f) cross section measurement at the new experimental area at CERN’s n_TOF facility - Stamatopoulos, A.; nTOF Collaboration, for the (HNPS Advances in Nuclear Physics, 2019)
The accurate knowledge of the neutron-induced fission cross-sections of actinides and other isotopes involved in the nuclear fuel cycle are essential for the design of advanced nuclear systems. These experimental data can also provide feedback for the adjustment of nuclear model parameters used in the evaluation process, resulting in further developments of nuclear fission models. In the present work, the 240Pu(n,f) cross-section was measured at CERN’s n_TOF facility over a wide range of neutron energies, from a few meV to several MeV, using the time-of-flight technique and a set-up based on MicroMegas detectors. This measurement was the first experiment to be performed in n_TOF’s new experimental area (EAR-2), which offers a significantly higher neutron flux compared to the existing experimental area. Preliminary results as well as the experimental procedure, including a brief description of the facility, the sample mounting, the read-out process and the data handling and analysis, are presented.